Evaluation of Root Canal Morphology of Mandibular Premolars Using Cone-beam Computed Tomography in Golestan Province, North of Iran - Sajed, Maryam; Alvandifar, Shiva; Mallahi, Maisa (Iranian Endodontic Journal, 2024)
Introduction: Successful endodontic treatment depends on completely clearing, shaping, and filling the prepared canals. Knowledge of the common and aberrant varying pulp anatomies is essential for suitable root canal treatment. Since, this anatomy is complex and varies morphologically in different populations. This study aims to determine the number of roots, canals, and evaluation of mandibular premolars canals using cone-beam computed tomography (CBCT) images in one of Iran’s northern provinces (Golestan). Materials and Methods: CBCT axial, coronal, and sagittal slices of two hundred and twelve mandibular premolars were analyzed to determine the number of roots and canals based on Vertucci type. The images were analyzed in a one-millimeter slice in mesiodistal and buccolingual dimensions based on gender. The data were analyzed using the Chi-score test to compare the components if the defaults were not established. A significance level of 0.05 was considered. Result: Of the two hundred twelve teeth evaluated, 130 (61.3%) were first premolars, and 82 (38.6%) were second premolars. Most first premolars (78.5%) and almost all second premolars (97.6%) had one root. Morphological types of root canals were identified based on Vertucci’s classification types I, II, III, IV, V, or VIII, and type I was the most frequent. There were no significant associations between number of roots and sex (P>0.05). Conclusion: Mandibular premolars mostly had one root and type I Vertucci morphology. The frequency of two-canal premolars was higher in the male population. Although the abundance of two or three roots with different morphologies was also observed, the possibility of the presence of an additional root canal should be considered.